STRATEGI PERSONAL BRANDING MAX5 OLEH STAR MEDIA NUSANTARA MELALUI MEDIA FACEBOOK - Suraya Suraya (Program Studi Ilmu Komunikasi Universitas Paramadina, 2015)
The purpose of this paper is to know about Star Media Nusantara Public Relations Strategy to do Personal Brandingof Max5 with Facebook. This research using a qualitative approach as a research methodology , this study using descriptive case studies . Results of the study : Star Media Nusantara used Facebook for PR Strategy in Personal Branding Max5. This activity phase about Phase I: Formative Research (analyzing the situation, analyzing the organization, analyzing the publics) Phase II: Strategy (establishing goals dan objectives, formulating action and response strategies, using effective communication) Phase III: Tactics (choosing communication tactics, implementing the strategic plan to used facebook for relationship Max5 with They Fans) Phase IV: Evaluative Research (evaluating the strategic plan). PR Strategy and tactic to doing with facebook because the information can be share and get in anywere and every where. Conclusion : Star Media Nusantara used PR strategy in personal branding of Max5 with facebook in another way, such as to share Max activity, picture and video. This is how to make a personal branding in society mind and how to buid relationship between Max5 and they fans. Suggest : We hope Star Media Nusantara make more strong a positioning statement for Max5 if they look in picture.Key words :Public Relations Strategy, Personal Branding, Facebook, Max5